Artificial Intelligence and Pattern Evidence: A Legal Application for AI - Juola, Patrick (2019)
Artificial intelligence changes everything, and almost no jobs will be immune. The application of AI to the practice of law is well-known and well-understood. In this paper, we present some aspects of the related disciplines of forensic science and specifically the development and analysis of “pattern [and impression] evidence.” We show that pattern evidence has a great need for AI.We discuss several applications in detail but focus mostly on the application of AI-based text analysis technology to forensic linguistics.